Discursive mobile phone practices & informal rules - Lloyd, Clare (Murdoch University, 2010)
This paper uses Discourse Analysis (DA) to investigate the socially constructed discursive practices of mobile phone use; specifically it examines the informal rules of mobile phone use. It qualitatively investigates mobile phone use within an Australian cultural context. ‘Discourse theory begins with the assumption that all objects and actions are meaningful, and that their meaning is a product of historically specific systems of rules’ (Howarth 2000, p. 8). Evidence of socially constructed textual meanings related to mobile phone use is found in the informal rules created (and practiced); those that in some way govern the use of mobile phones. The research reveals that there are divergences and inconsistencies within the discourse of mobile phone use, and illustrates that individuals make differing personal choices in similar social contexts.